INNOVATIVE SOLUTION FOR BIPA: ENHANCING READING SKILLS AND CULTURAL UNDERSTANDING THROUGH INTERACTIVE MULTIMEDIA - Karuniawan, Yoga; Herman Dwi Surjono (Jurnal Pendidikan (Teori dan Praktik), 2025)
This research addresses the low reading ability of beginner-level BIPA students in understanding Indonesian cultural materials, attributed to complex vocabulary, grammar, and contextual themes. It analyzes the feasibility, practicality, and effectiveness of interactive multimedia integrated with a self-directed learning model to enhance reading skills and cultural understanding. Using a quantitative experimental approach with a one-group pretest-posttest design, 30 A1-level BIPA students were selected through purposive sampling. Data were collected via expert validation, practicality questionnaires, and culture-based reading tests. Results indicate: (1) high feasibility by media (3.81/4) and material experts (3.56/4); (2) very high practicality ratings by lecturers (3.72/4) and students (3.56/4); and (3) moderate effectiveness (N-gain 0.63), with average scores rising from 62.33 (pre-test) to 86.16 (post-test). The study concludes that pedagogically designed interactive multimedia strengthens linguistic and cultural competencies through contextual content, intuitive design, and self-directed learning flexibility. This model offers an innovative, adaptive solution for technology-based language education in cross-cultural contexts.